Moving Tourism places: displacement and guided tours in Salta (Argentina) (Huellas, 2021)
The article addresses the role of tourist movement in defining Salta (Argentina) as a tourist place. In order to do that, specific practices of displacement (guided tours hired by tourists) were observed. As a preliminary study, the paper discusses traditional approaches to guided tours as highly standardized and prescribed experiences. And it also exposes the active participation of the different actors that take part in the tours. In addition, the paper seeks to contribute to the understanding of tourist places considering tourist movement and specially the practices that shape it.